Beyond Agenda Setting: Does Media Coverage Of Immigration Lead To Anti-Immigrant Behavior? - Krupenkin, Masha; Hill, Shawndra; Rothschild, David (2020)
This paper studies the influence of news coverage of immigrants on anti-immigrant beliefs and behaviors. Using news transcripts, Google Trends data, and a novel dataset of Bing web searches for immigration-related topics, we examine the role of the 2016 election and the resulting media coverage on searches for how to report immigrants to ICE, as well as searches about immigrant crime and welfare dependency. We find not only significant and sustained increases in media discussion of immigrant crime after the Trump inauguration, but a similarly sustained increase in searches for how to report undocumented immigrants that is strongly correlated with the daily volume of immigration crime coverage. Crime and welfare searches about immigrants are also highly correlated with immigrant crime and welfare news volume, respectively. Using timestamped searches for immigration during Trump and Obama speech broadcasts, we confirm the causal effect of anti-immigrant media broadcasts on searches for immigration and crime, welfare, and reporting to ICE. Overall, the findings show that media depictions of immigrants can have a strong impact on not only attitudes but real world behaviors.